Monitoring of Oral Anticoagulation by an Amidolytic Factor X Assay - Lämmle, B; Bounameaux, H; Marbet, G A; Eichlisberger, R; Duckert, F (Thrombosis and Haemostasis, 1980)
The validity of the amidolytic Factor X assay for the control of long term oral anticoagulation (OA) was investigated in 42 patients randomized into 2 groups; PT group (anticoagulant dosage according to PT) and F. X group (anticoagulant dosage based on F. X). An independent expert's dosage according to F. X served for analysis in the former group. In the F. X group the F. X based dosage was considered valid only when not differing by more than 15% from the expert's PT based dosage.Confirming the good correlation between PT and F. X the study further demonstrates that the changes from one control to the next one, ΔPT and ΔF. X, too, are significantly correlated (r = 0.58, p & 0.001, n = 217). In over one third of the periods the dosage proposals based on PT and F. X were identical and differed by more than 15% in only 12/217 instances.Our results justify a large trial on the control of OA by the amidolytic F. X assay.
Keywords: Oral anticoagulation; Monitoring; Factor X; Amidolytic assay; Prothrombin time; Chromogenic substrate